2018
DOI: 10.3390/pharmaceutics10040241
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Excretive Characterization of Main Components in Herb Pair Notoginseng-Safflower and Single Herbs by LC–MS/MS

Abstract: The herbal medicine combination of notoginseng-safflower has been commonly used clinically for the prevention and treatment of cardiovascular diseases. A reliable liquid chromatography-tandem mass spectrometry (LC–MS/MS) method was developed for simultaneous determination of six bioactive components (hydroxysafflor yellow A, notoginsenoide R1, ginsenoside Rb1, Re, Rd, and Rg1) in rat urine and feces after oral administration of notoginseng total saponins (NS), safflower total flavonoids (SF), and the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that in addition to notoginsenosides and ginsenosides, the rhizome and root of P. notoginseng also contains dencichine, flavonoids, amino acids, organic acids, sugars, etc. [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that in addition to notoginsenosides and ginsenosides, the rhizome and root of P. notoginseng also contains dencichine, flavonoids, amino acids, organic acids, sugars, etc. [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%